2019
DOI: 10.5327/z1679443520190443
|View full text |Cite
|
Sign up to set email alerts
|

Disability and functioning assessment of women with RSI/WRMSDs: the use of the ICF checklist

Abstract: | Background: Comprehensive approaches using the International Classification of Functioning, Disability and Health (ICF) Checklist have been adopted to give more visibility to demands related to specific health situations. Objective: To analyze the incapacity and functioning associated with activity/participation and environmental factors of female workers with repetitive strain injury/work-related musculoskeletal disorders (RSI/WRMSDs) using workers’ narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
2
0
2
Order By: Relevance
“…Studies 23 24 on other health conditions that used the ICF checklist highlighted the value of this tool. 23 24 Magalhães et al 23 evaluated work-related repetitive stress disorders/ musculoskeletal disorders, and found that, the ICF enabled the identification of the clinical and social aspects experienced by patients during rehabilitation and their return to work.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies 23 24 on other health conditions that used the ICF checklist highlighted the value of this tool. 23 24 Magalhães et al 23 evaluated work-related repetitive stress disorders/ musculoskeletal disorders, and found that, the ICF enabled the identification of the clinical and social aspects experienced by patients during rehabilitation and their return to work.…”
Section: Discussionmentioning
confidence: 99%
“…Studies 23 24 on other health conditions that used the ICF checklist highlighted the value of this tool. 23 24 Magalhães et al 23 evaluated work-related repetitive stress disorders/ musculoskeletal disorders, and found that, the ICF enabled the identification of the clinical and social aspects experienced by patients during rehabilitation and their return to work. Silveira et al 25 evaluated individuals with Parkinson disease, and the results demonstrated that the ICF seems to have good ability and sensitivity to address aspects of functionality regarding this disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations